Pregnancy Outcomes in Anglophone Quebec : Recent Research Results - Auger, Nathalie (2023)

Déclaration du QCGN concernant le projet de loi 15 et le recours au bâillon - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Bill 15 and Closure - Quebec Community Groups Network (QCGN) (2023)

Bill 15 Petition Gathers 6400 Signatures in 16 Days - Quebec Community Groups Network (QCGN) (2023)

La pétition concernant le projet de loi 15 recueille 6400 signatures en 16 jours - Quebec Community Groups Network (QCGN) (2023)

Il n'y a plus de temps à perdre avant l’imposition par le gouvernement d’une centralisation massive des services de santé et des services sociaux – à quoi s'ajoute une nouvelle menace à l'accès à l'anglais - Quebec Community Groups Network (QCGN) (2023)

No Time to Waste before Government Imposes Massive Centralization of Health and Social Services – and Adds a New Threat to English Access - Quebec Community Groups Network (QCGN) (2023)

Lancement d’une pétition pour la révision de la réforme radicale du réseau de la santé prévue par le projet de loi 15 - Quebec Community Groups Network (QCGN) (2023)

Petition demands rethink of Bill 15’s radical revamp of Health Care Network - Quebec Community Groups Network (QCGN) (2023)

[Three in Every Classroom : Supporting Young Carers in Schools] - Fitzpatrick, Olivier (2023)

Brief to the Senate Standing Committee on Official Language’s Study of Matters Relating to Minority-language Health Services - Quebec Community Groups Network (QCGN) (2023)

Seniors Action Quebec Presentation on Study Matters Relating to Minority-Language Health Services - Seniors Action Quebec (SAQ) (2023)

English-language Health and Social Services Access in Québec - Community Health and Social Services Network (CHSSN) (2023)

Seniors Action Quebec Brief : Vieillir et vivre ensemble, chez soi, dans sa communauté, au Québec (VVE) - Plan d’action 2024-2029 - Seniors Action Quebec (SAQ) (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations to the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)

Make the Case Report : Access to Senior Care in English in Quebec : A research analysis of English language rights in Quebec health care and access to the SAPA program for English-speaking seniors in Quebec - Quebec Community Groups Network (QCGN) (2023)
This report discusses and details one of the AJEQ Project’s candidate issues of research: access to senior health care services in English in Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Projet Accès à la justice en anglais : Services de soins aux personnes âgées en anglais au Québec : Sommaire du rapport final et recommandations au Ministère de la Santé et des Services sociaux - Quebec Community Groups Network (QCGN) (2023)

Access to Justice in English Project : Senior Care Services in English in Quebec - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.
Parallel title : Executive Summary of Final Report and Reccomendations to the Ministry of Health and Social Services

Senior Care Services in English in Quebec : Executive Summary of Final Report and Recommendations of the Ministry of Health and Social Services - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English Project (“the AJEQ Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec. The second issue studied by the Project was access to health care services for seniors in English through Quebec’s SAPA program (Soutien à l’autonomie des personnes âgées). The issue was selected on the basis of prior research conducted by the AJEQ Project, including a population survey of 1,601 English-speaking Quebecers conducted by Quorus Consulting Group in September 2021, which revealed that hospitals and CLSC care were among the most widely accessed provincial government services by English-speaking Quebecers, and that more than one in three English-speaking Quebecers who had accessed these services in the past two years found it difficult to do so in English. The issue of senior care was under close scrutiny at the time the issue was selected, in the wake of the COVID-19 pandemic and the subsequent coroner’s inquiry into pandemic-related deaths at seniors’ residences across Quebec.

Impact Report 2022-2023 - 4Korners (2023)

Committee for Anglophone Social Action Annual Report - Committee for Anglophone Social Action (CASA) (2023)

Annual Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)

CHSSN À propos de Nous / Who We Are - Community Health and Social Services Network (CHSSN) (2023)
Through a program called the Networking and Partnership Initiative (NPI), the CHSSN supports 23 community organizations serving English-speaking communities across the province in their efforts to collaborate with partners to improve access to health and social services in English (see map).

CHSSN Senior Wellness Centre Initiative Activity Report Year 2 (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 10

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 10

Investing in the Vitality of English-speaking Quebec / Investir dans la vitalité du Québec d'expression anglaise - Community Health and Social Services Network (CHSSN) (2023)
Keywords: Official Language Minority Community (OLMC)

Networking and Partnership Initiative / Initiative de réseautage et de partenariat (NPI) - Community Health and Social Services Network (CHSSN) (2023)

Senior Wellness Centre Initiative Activity Report (2022-2023) - Community Health and Social Services Network (CHSSN) (2023)

Annual Report 2022-2023 - English Speaking Catholic Council (2023)

2023 Report : "An Analysis of the Demographic and Socio-Economic Characteristics of Quebec's English-Speaking Community Compared to the French-Speaking Population" with a Focus on the RTS de la Montérégie-Oues - Montérégie West Community Network (MWCN) (2023)

Health and Social Services Career Opportunities Training Guide : Eastern Townships Region - Townshippers' Association; Dialogue McGill (2023)